Pengaruh Pendapatan Transfer Daerah Terhadap Tingkat Kemiskinan - Timoer Warih Rianggara; Warsito Kawedar (Universitas Warmadewa, 2025)
Poverty remains a prevalent issue across all nations, including developing countries such as Indonesia. This study aims to analyze the impact of transfer income on poverty levels across all provinces in Indonesia. The research population comprises all provinces in Indonesia, with a sample of 34 provinces observed from 2018 to 2022, resulting in a total of 170 samples. This study employs a quantitative method with a multiple regression approach to examine the relationships between variables. The data used are secondary, obtained from the DPJK and BPS websites. The regression estimation model applied is the Random Effect Model (REM), also known as the Generalized Least Squares (GLS) model. The findings indicate that transfer income has a negative and significant impact on poverty levels. The General Allocation Fund (DAU) has a positive and significant effect, while the Special Allocation Fund (DAK) and Revenue Sharing Fund (DBH) have a negative and significant impact on poverty levels.